Preexisting influenza-specific CD4 + T cells correlate with disease protection against influenza challenge in humans - Wilkinson, T; Li, C; Chui, C; Huang, A; Huang, A; Perkins, M; Liebner, J; Lambkin-Williams, R; Gilbert, A; Oxford, J; Nicholas, B; Staples, K; et al. (2012)
Protective immunity against influenza virus infection is mediated by neutralizing antibodies, but the precise role of T cells in human influenza immunity is uncertain. We conducted influenza infection studies in healthy volunteers with no detectable antibodies to the challenge viruses H3N2 or H1N1. We mapped T cell responses to influenza before and during infection. We found a large increase in influenza-specific T cell responses by day 7, when virus was completely cleared from nasal samples and serum antibodies were still undetectable. Preexisting CD4 +, but not CD8 +, T cells responding to influenza internal proteins were associated with lower virus shedding and less severe illness. These CD4 + cells also responded to pandemic H1N1 (A/CA/07/2009) peptides and showed evidence of cytotoxic activity. These cells are an important statistical correlate of homotypic and heterotypic response and may limit severity of influenza infection by new strains in the absence of specific antibody responses. Our results provide information that may aid the design of future vaccines against emerging influenza strains. © 2012 Nature America, Inc. All rights reserved. © 2012 Nature America, Inc. All rights reserved.